The Readiness of Private Vocational School Students in Pringsewu Regency in Learning Local History Teaching Materials KH Gholib's Struggle - Yoga Fernando Rizqi; Djono Djono; Susanto Susanto (Universitas Sebelas Maret, 2020)
By utilizing the development of technology and communication in the 21st century, it is hoped that it can meet the needs of students related to local-based history learning. With the current development of technology and communication, we have felt the impact such as the emergence of various applications with features that can be used to compile and shape teaching materials with digital displays, such as products that have been compiled with the theme KH. Ghalib's struggle. The application used is Flip PDF Professional 2.4.9.18. By utilizing this technology, it is hoped that it can improve students' readiness to study history, especially those based locally. The methodology used in this research is descriptive qualitative. This method is carried out by distributing questionnaires containing questions about the readiness of Pringsewu Private Vocational School students. The findings in two private schools in Pringsewu Regency, namely SMK Nurul Huda and SMK KH Ghalib, show the readiness of students in learning local history teaching materials. Based on the results of the study, it can be concluded that by utilizing technological and communication advances it can trigger student readiness to learn, especially local-based history learning.